Effects of cheese ingestion on muscle mass and strength in possible sarcopenia women: an open-label, parallel-group study - Jingsi Chen; Yan Wang; Yifan Yang; Chenxi Su; Mingquan Wang; Yilin Chen; Jing Yang; Xiaofang Chen; Yingyao Wang; Liqiang Qin (Nutrition & Metabolism, 2024)
Abstract Background Nutrient-rich cheese supplements were demonstrated to have improvements in markers of sarcopenia in healthy elders. However, the potential effects of cheese in individuals with possible sarcopenia remain unknown. Method This 90-day randomized controlled trial (RCT) included 68 women aged 60–80 years with possible sarcopenia in China, who were randomly assigned to three groups: Control group (CG), Original cheese group (OG: 9.0 g protein; 322.8 mg calcium), and Golden cheese group (GG: 12.7 g protein; 802.1 mg calcium). OG and GG were instructed to consume their habitual diet along with 4 slices of supplied cheese, while CG was directed to maintain their usual dietary habits. Face-to-face interviews, anthropometric measurements, and blood sample collection were conducted at baseline, midway (60 days), and the end of the trial. Result At the end of the trial, the primary outcome, changes of Skeletal Muscle Mass Index (SMI) were found to be higher in OG (0.18 ± 0.02 kg/m2) and GG (0.14 ± 0.02 kg/m2) compared to CG (0.09 ± 0.02 kg/m2). The secondary outcome, changes of handgrip strength were higher in GG (1.82 ± 4.16 kg) than CG (-0.61 ± 3.78 kg). There were no significant differences in makers for muscle function between three groups (P > 0.05). In the self-comparison, Creatinine/Cystatin C significantly increased in both OG and GG. In addition, OG had a significant increase in changes of free and total carnitine compared to CG. Conclusion Both golden and original cheese supplementation enhanced muscle strength and mass in older women with possible sarcopenia. The mechanism behind this effect may be linked to muscle cell energy metabolism. Trial registration The present study was registered in the Chinese Clinical Trial Registry with the registration number ChiCTR2300078720 (retrospectively registered, 20231215).